Análise de desgaste de um pistão de bomba de injeção a diesel combinando ensaio experimental e simulação por elementos finitos - Farias, Joao Guilherme (2016)
The most common way to study wear of mechanical components and evaluate the parameters that affect it is through experimental tests. In addition, studies using numerical simulations with the Finite Element Method in combination with mathematical models have helped to understand some physical principles, as well to estimate the effects of wear. Within this context it is inserted this thesis, which goal is to study the tribological behavior of the plunger-pump body of a diesel injection system through experimental tests and numerical simulations. A device is developed and built for experimental sliding tests on a tribometer. Dry tests are performed with variation of normal forces and sliding distances. Results are integrated with a numerical model through a sub-routine that applies the wear along the simulation. The numerical model is developed by finite element method in order to represent the experimental tests and reproduce the wear in the plunger surface. The experimental results show different wear behaviors and mechanisms. In the beginning of the tests, the behavior is stable, with smaller wear rate and mechanisms with predominance of plastic deformation. At the end of this period, the number of wear particles in the interface and attached to the opposing surface is increased, generating abrasion, increasing the wear rate, up to the total break of the plunger titanium-nitride coating. The sub-routine applies the wear with good agreement with experimental tests. With the results of the numerical model, it is possible to evaluate the components behavior, taking into account the wear evolution in the plunger, besides estimating the wear coefficient for the evaluated contact pair.